A Duna Medical Center Kft. vagyoni, pénzügyi, jövedelmezőségi helyzetének elemzése a számviteli beszámolók alapján - Veresné Pesti Ilona (2018)
In my thesis I aim to focus on Duna Medical Center Limited profitability and financial circumstances based on it’s financial statements. During my calculations and assesments I applied the 3 years data of the company’s balance sheet and profit and loss statement. I took my conclusions by being absorbed in the relevant literature and applying the knowledge acquired in my recent studies. The Duna Medical Center is an outpatient clinic, which provides one day surgeries and variuous inpatient services, started it’s operation on August of 2015 in Budapest. It’s undoubtedly the first private healthcare institute which provides comprensive services in 45 disciplines on a world class level. Nowadays the private healtcare industry claims increasing share from the healthcare market. Conclusion can be taken from the trends and tendencies as this steady increase will positively continue in the near future. Due to the technological evolution the cost of medical services will grow. The government will less likely to be able to provide the sufficient finacial resources for the public healthcare sector. That will create higher demand towards the private institutes. In the first part of my thesis I intend to bring the attention to the Hungarian healtcare system with it’s effectiveness including the private health sector. In the following chapter I present the reader with information regarding Duna Medical Limited, as well as it’s fundation, way of operation and it’s future plans. In the major part of my writing I’m going to break down the company’s balance sheets and P&L statements to their elements and perform a deep analysis. During this I will mostly fall back on analitical methods and processes tought by various financial subjects. In it’s first three years the Duna Medical Center Ltd. generated loss which only happened due to the early phases of business operation. The range and number of healthcare services provided by the company extend rapidly, what results in countinous growth of sales revenue. The top value for Duna Medical Center Ltd is to provide outstanding level of service as well in the outpatient as in the inpatient business unit.